Valuing maternal, newborn, child and adolescent health for societal progress – Going beyond the economic orthodoxy of gross domestic product. (6th February 2023) - Meka, Kiran; Jacob, Chandni M.; Modi, Neena; Bustreo, Flavia; Di Renzo, Gian Carlo; Malamitsi‐Puchner, Ariadne; Briana, Despina; Iaia, Domenico G.; Fogstad, Helga; Tamvada, Jagannadha P.; Moreno, Ivan Ochoa; Hanson, Mark
Abstract: Aim: In view of the long‐standing recognition that gross domestic product (GDP) does not capture the unremunerated work largely conducted by women upon which societal well‐being depends, to discuss the implications for GDP of maternal, newborn, child and adolescent health (MNCAH), and its influences on health, well‐being and prosperity across the life course and across generations. Methods: A wide‐ranging discussion of the informal think‐tank The Venice Forum was held over two days, with inputs from invited experts in person and online. Results: There was consensus that a strong case could be made for inclusion of unremunerated work largely conducted by women as a positive contribution to GDP in view of its impact on future health and prosperity, and conversely exclusion from GDP of outputs from industries which harm health. Conclusion: Taken with the current challenges from COVID, climate change and conflict, there is a compelling need to redefine economic progress through equitable models and metrics that incorporate short‐/medium‐/long‐term societal value of activities that improve MNCAH.